Zika Virus Infection During Research Vaccine Development: Investigation of the Laboratory-Acquired Infection via Nanopore Whole-Genome Sequencing - Bang, Eunsik; Oh, Sujin; Chang, Ho Eun; Shin, Il Seob; Park, Kyoung Un; Kim, Eu Suk (Frontiers in Cellular and Infection Microbiology, 2022)
Zika virus (ZIKV) emerged as a serious public health problem since the first major outbreak in 2007. Current ZIKV diagnostic methods can successfully identify known ZIKV but are impossible to track the origin of viruses and pathogens other than known ZIKV strains. We planned to determine the ability of Whole Genome Sequencing (WGS) in clinical epidemiology by evaluating whether it can successfully detect the origin of ZIKV in a suspected case of laboratory-acquired infection (LAI). ZIKV found in the patient sample was sequenced with nanopore sequencing technology, followed by the production of the phylogenetic tree, based on the alignment of 38 known ZIKV strains with the consensus sequence. The closest viral strain with the consensus sequence was the strain used in the laboratory, with a percent identity of 99.27%. We think WGS showed its time-effectiveness and ability to detect the difference between strains to the level of a single base. Additionally, to determine the global number of LAIs, a literature review of articles published in the last 10 years was performed, and 53 reports of 338 LAIs were found. The lack of a universal reporting system was worrisome, as in the majority of cases (81.1%), the exposure route was unknown.